THRUSTERS, SCOOPERS, SCROUNGERS AND SQUIRRELS: A TAXONOMY OF PUBLIC SECTOR AUDIT AND ACCOUNTABILITY MECHANISMS - Kells, Stuart (The journal of contemporary issues in business and government, 2010)
The concept of public sector accountability is attracting a great deal of attention both inside and outside the academy. Performance auditing is one of a large and growing number of mechanisms that are used to enhance accountability. Though it is an important and prominent feature of public administration in many countries, performance auditing is often said to be difficult to define. Kells and Hodge (2009) proposed a framework for defining performance auditing, which they then used to study other types of accountability and review mechanisms, including management audits, whistleblower laws, freedom of information laws, open book policies and citizen engagement models. This paper formalizes and generalizes Kells and Hodge’s framework. After expressing the framework using set function notation and concepts from game theory, the paper then applies the elements of the framework to develop a general taxonomy of audit and accountability mechanisms. The taxonomy is presented graphically, and then in the form of a new terminology of mechanism types. The paper concludes with directions for future research regarding the design and evaluation of accountability mechanisms